Variable Importance Analysis in Imbalanced Datasets: A New Approach - Ismael Ahrazem Dfuf; Joaquin Forte Perez-Minayo; Jose Manuel Mira Mcwilliams; Camino Gonzalez Fernandez (IEEE Access, 2020)
Decision-making using machine learning requires a deep understanding of the model under analysis. Variable importance analysis provides the tools to assess the importance of input variables when dealing with complex interactions, making the machine learning model more interpretable and computationally more efficient. In classification problems with imbalanced datasets, this task is even more challenging. In this article, we present two variable importance techniques, a nonparametric solution, called mh-χ2, and a parametric method based on Global Sensitivity Analysis. The mh-χ2 employs a multivariate continuous response framework to deal with the multiclass classification problem. Based on the permutation importance framework, the proposed mh-χ2 algorithm captures the dissimilarities between the distribution of misclassification errors generated by the base learner, Conditional Inference Tree, before and after permuting the values of the input variable under analysis. The GSA solution is based on the Covariance decomposition methodology for multivariate output models. Both solutions will be assessed in a comparative study of several Random Forest-based techniques with emphasis in the multiclass classification problem with different imbalanced scenarios. We apply the proposed techniques in two real application cases in order first, to quantify the importance of the 35 companies listed in the Spanish market index IBEX35 on the economic, political and social uncertainties reflected in economic newspapers in Spain during the first quadrimester of 2020 due to the COVID-19 pandemic and second, to assess the impact of energy factors on the occurrence of spike prices on the Spanish electricity market.